Exploring the Underuse of HPV Vaccination Among Women in Pakistan, A Clinical Evaluation of an Urgent Public Health Threat - Nosheen Sikandar Baloch, Hanana Hameed, Aisha Taj, Syeda Shaista Waheed, Allah Bux Mushtaq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cervical cancer is a leading cause of cancer-related morbidity and mortality among women worldwide, especially in low- and middle-income countries like Pakistan. Although human papillomavirus (HPV) vaccination is a proven preventive measure, its uptake in Pakistan remains extremely limited. This study aimed to assess the awareness, vaccination status, and barriers to HPV vaccine acceptance among women in Pakistan. Methods: A descriptive, cross-sectional study was conducted from January 2022 to January 2023 at two tertiary care hospitals: Sandeman Provincial Hospital (SPH), Quetta, and Liaquat National Hospital (LNH), Karachi. A total of 150 women aged 15 to 45 years attending gynecology outpatient clinics were interviewed using a structured questionnaire. Data were analyzed using SPSS version 25.0, with Chi-square test used to determine associations. Results: Only 15.3% of participants had heard of HPV, and 21.3% were aware of the HPV vaccine. Vaccine uptake was extremely low, with only 6.7% of respondents having received at least one dose. The most commonly reported barriers to vaccination were lack of awareness (63.6%), fear of side effects (48.6%), cost (46.4%), cultural or religious concerns (28.6%), and unavailability at local health centers (20%). Higher education level and urban residency were significantly associated with greater awareness and uptake (p < 0.05). Conclusion: HPV vaccination remains severely underused among Pakistani women due to a combination of informational, economic, cultural, and systemic barriers. Public health interventions are urgently needed, including nationwide education campaigns, healthcare provider training, and integration of HPV vaccination into the national immunization program. Keywords: HPV vaccine, cervical cancer, women’s health, Pakistan, awareness, public health barriers